The poetry of Anton Schnack - Waller, C (2014)
This thesis is the first academic treatment of the poetry of Anton Schnack (1892-1973): his work is not well known, even in Germany. Methodologically the thesis takes a combined literary, historical and biographical approach, exploring the complex and sometimes deceptive relations between his poetry and the turbulence of his time. The primary aim of the thesis is to show that Tier rang gewaltig mit Tier (1920) is a uniquely innovative volume of war poetry which, to be fully appreciated, needs to be assessed against the background of previous German war poetry and the development of the sonnet cycle. It is placed in the context of Schnack’s other lyrical work, particularly of the three volumes of Expressionist poetry which immediately preceded it and which themselves are analysed as examples of a very powerful kind of Expressionism. Schnack did not publish his next volume of verse until 1936, and three further collections emerged in quick succession between 1947 and 1953. These four collections are examined in detail in the context of Schnack’s decision to stay in southern Germany and to maintain a consistently low profile. The thesis begins with a general introduction to Schnack’s life and work and makes specific reference to his contemporary and current standing among literary historians and critics. Chapter Two focuses on the three volumes of Expressionist verse and documents the cultural circles which he frequented in Munich and the numerous Expressionist magazines and periodicals to which he contributed. The next three chapters are dedicated to Tier rang gewaltig mit Tier and examine it with reference to its poetic form as a cycle of sonnets and of its merits and status as war poetry. The final chapter pays particular attention to Schnack’s life in the Third Reich, situating the single collection he published during that era among the literary works of Inner Emigration, before analysing his three post-war collections.